A Study to Assess the Effectiveness of Body Mechanics Training Programme on Reducing Low Back Pain Among Nursing Officers Working in Selected Hospitals, Bangalore - Aravindhan K (International Journal of Orthopedic Nursing and Practices, 2024)
Background: Low Back Pain (LBP) is a common work related injury and costly problem among the nursing profession. Numerous studies indicate a greater occurrence of back pain and work-related back injuries among nursing officers in comparison to other occupations. Prevention of LBP is a very important technique to maintain proper body mechanics. This study aimed to assess the effectiveness of body mechanics training programme on reducing low back pain among nursing officers working in KIMS Hospital & Research Centre, Bangalore. Objectives: 1. The objectives of this study were: 1. To assess the prevalence of low back pain (LBP) among nursing officers. 2. To evaluate the efficacy of a body mechanics training program in decreasing LBP among nursing officers. 3. To determine the correlation between LBP scores of nursing officers and specific biophysical factors. The research methodology employed a quasi-experimental design utilizing a single-group pre-test and post-test time series approach, with the selection of participants done through non-probability purposive sampling. Data was gathered from 40 nursing officers utilizing the Defence and Veterans Pain Rating Scale (DVPRS). After the demonstration of body mechanics, training program was implemented and post-test was conducted on 7th, 14th, and 21st days by using same tool to compare difference between observations. Results: The overall pretest showed that majority (55%) of nursing officers had moderate LBP, followed by 37.5% of severe LBP and 7.5% of nursing officers had mild LBP and in the post-test, it was observed that the level of LBP slowly reduced during observation-I, observation-II, and observation-III respectively, and enhancement in the mean difference in LBP among nursing officers were highly significant with p-value <0.0001. There was a significant association between LBP and biophysical variables, such as the number of patients lifted per day, with a chi-square value of 11.64 and a p-value of 0.02. Interpretation and Conclusion: In this study, it was revealed that a body mechanics training programme was effective in reducing LBP.
Keywords: DVPRs; KIMS hospital; LBP; body mechanics training programme; nursing officers